Strategi Kepala Madrasah dalam Memenuhi Sarana dan Prasarana untuk Meningkatkan Kegiatan Belajar Mengajar di Madrasah Aliyah Hidayatul Mubtadiin Jati Agung Lampung Selatan - Said Anfasyah (Departement of Mathematics Education, 2024)
The purpose of this study is to investigate the methods used by the Madrasah Head to enhance the infrastructure and facilities available for teaching and learning at Madrasah Aliyah Hidayatul Mubtadiin. Mubtadiin Hidayatul. This study employs a qualitative, descriptive methodology, and data is gathered through documentation, non-participant observation, and guided interviews. The head of the madrasah, the administrative team, and one madrasah teacher are the sources of the data. The phases of data reduction, data display, and conclusion drawing/verification are used in the data analysis technique. In the interim, member checks, triangulation, prolonged participation, and observation are used to verify the accuracy of the data. The study's findings demonstrate that: The madrasa head's first approach to providing infrastructure and facilities to enhance teaching and learning activities is planning. This approach consists of three programs: needs analysis, goal formulation, and learning material development. Second, the madrasah budget plan (RKAM) is used for purchase; additional funds are redirected to pay for infrastructure and facilities, like tools for instructional activities. Third, facility and infrastructure maintenance is always accompanied by assessments and enhancements. Fourth, the process of erasing infrastructure and facilities involves first removing the inventory data listing of these items, gathering damaged commodities in one location, and either selling or destroying them. The fact that each madrasa authority takes action to maintain the infrastructure and facilities that are already in place serves as a supportive component. The fact that certain teachers do not give a damn about the infrastructure and amenities this madrasah has is the impediment.